KARAKTERISTIK PERMEN JELLY WORTEL (DAUCUS CAROTA L.) DALAM BERBAGAI KONSENTRASI GELATIN - Akhmad Mustofa, Sriyono, Linda Kurniawati & (Universitas Slamet Riyadi Surakarta, 2016)
Carrots (Daucus carota L.) is one of the agricultural commodities in Indonesia which contains provitaminA. Beta?Caroten is known to maintain eye health. This research aimed to determine the ratio of gelatinconcentration and optimal concentration of carrot juice to produce carrot jelly candy that has quality andpreferred by consumers. The research was canducted using a completely randomized design (CRD) factorialconsisting of 2 factors. The first factor was concentration of gelatin i.e 3%, 5%, 7%. 9% and the second factorwas the concentration ratio of carrot juice i.e 50%, 75%, 100%. The results showed that the best combinedtreatment was consist of 7% gelatin concentration and 75% of carrot juice. This treatment had 32,500% ofmoisture content, 1,970% of ash, 4.88% of reducting sugar, 5.12 of acidity, 103.115 mg/g of Beta?Carotene, orangecalor (2,500); tasteless carrots (1,500); chewy (3,083) and preferred by consumers (2.667).Key words: Jelly Candy, Carrot, Calculate, Gelatin